Evolución de los parámetros ambientales en las centrales de generación eléctrica en la región Loreto – 2021 - Vargas Rodriguez, Juan Felipe (2023)
The general objective of this research work was to evaluate the evolution of the environmental parameters in the activities of the power generation plants of Loreto, based on the monitoring of these parameters from 2018 to 2021. The research, due to its approach, was quantitative of the type analytical, predictive, horizontal and retrospective. The information was obtained from the Monitoring Reports of the Environmental Parameters of the Power Generation Plants in the Loreto Region 2018 to 2021. The representative sample is defined by seven (07) Power Generation Plants with a power generation capacity greater than 500 KV: Iquitos, Requena, Caballo Cocha, Contamana, Tamshiyacu, Nauta and Orellana. The technique consisted of initially building a database to process the information from the time series of the quarterly environmental monitoring of the power plants under study, expressing them with trend graphs and their subsequent mathematical modeling to predict changes in the parameters. environmental factors evaluated, using the HoltWinter mathematical model with exponential smoothing. The Results show that: The Environmental noise in the Loreto power plants is below the maximum limit allowed in the noise environmental quality standard. In general, the intensity of the electric field in the power plants included in the study is well below the maximum permitted level of 4166.67 Volts, according to Supreme Decree No. 010-2005-PCM.